Fifteen wild Decembers - Powell Karen (Europa Editions, 2023)
A creative re-imagining of the short life of Emily Brontë, one of England's greatest writers. Isolated from society, the Brontë children spend all their time inventing elaborate fictional realms or roaming the wild moors above their family home in Yorkshire. When the time comes for them to venture out into the world to earn a living, each of them struggles to adapt, but for Emily the change is catastrophic. Torn from the landscape she loves and no longer able to immerse herself in the fantastical world of Gondal that she and her younger sister Anne have created, she is simply unable to function. As a child, Emily witnessed a rare natural phenomenon. After weeks of rain, the peaty soil on Crow Hill became so sodden that the earth exploded. Since then, her life has been dogged by tragedy and repeated failures. Her sisters are desperate to escape their unsatisfactory work as governesses and now the life of her brother Branwell, the hope of the family, is in turmoil. To the outside world, Emily appears taciturn, unexceptional; but beneath the surface her mind is in a creative ferment, ready to burst forth. As the pressure on her grows, another violent phenomenon is about to take place, one that will fuse her imaginary world of Gondal with the landscape Emily loves so passionately, and which will change the literary world forever.
Keywords: Brontë Emily 1818-1848 Roman; Moeurs et coutumes Grande-Bretagne 19e siècle; Yorkshire (GB)